The intention to cyberbully and cyberbullying behaviour among undergraduate students - Abdul Rashid, Muhammad Shawal; Mohamed, Shafizan; Tengku Mohd Azman, Tengku Aisha (IIUM Press, International Islamic University Malaysia, 2017)
The ever-expanding communication technologies and high usage of the Internet among youths have created an avenue for an emerging social problem, cyberbullying. This study analyses the contributing factors to cyberbullying behaviour; 397 Muslim undergraduate students participated in the study and it has yielded some interesting results. Underpinned by the theory of planned behaviour, this study found some support for the theory. Specifically, perceived social pressure (subjective norms) has been identified as the most important predictor, followed by attitudes towards cyberbullying. However, perceived behavioural control was not significantly related to the toxic behaviour. Also, an additional variable, religiosity, has been added into the framework and the result suggested that there is a significant negative relationship with the intention to perpetrate cyberbullying. Overall, these results indicate the need to address the anti-social behaviour by related-parties and preventive measures need to be taken in order to promote pro-social behaviours in the online environment.